Criminal Tax Law Perspective on General Criminal Law in Indonesia - Fajarudin, Ibnu; Arwanto, Bambang; Suyono, Joko; Rahayuana, Niken Arief (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: Taxes are income that is very important for the balance of state income. Currently, tax is the largest contributor to the Indonesian APBN. In tax obligations, taxpayers carry out their rights and obligations using the self-assessment method. Tax avoidance and even tax evasion are very likely to occur. Enforcement of criminal law in the field of taxation (tax enforcement) in order to increase taxpayer compliance. This research aims to look at the perspective of tax criminal law on general criminal law in Indonesia. This research uses a descriptive analytical method by collecting several literacy sources and discussing them in paragraph form. Design/methodology/approach: The self-assessment method allows taxpayers to commit tax violations, tax violators as long as the perpetrator has committed an act or actus reus which is a prohibited act and knows that his actions cause losses to other parties, then it is sufficient for the perpetrator to be subject to criminal sanctions/punishments as stipulated in the provisions of ignoring the element of mens rea, as stipulated in the Tax Criminal Law (UU HPP). Findings: Of the criminal acts contained in the Criminal Code, criminal acts in the field of taxation will always be related to and include the formulation of other criminal acts, whether general or specific. Paper type: Review paper.